Strengthening Community Capacity in Muncangkopong Village, Cikulur, Lebak, Banten Through Participatory-Based Community Service Programs - Dadan Sunandar; Hasan Maulana; M. Rifki Annaufal; Dede Ihmat; Agnat Wiqoyati (STAI Publisistik Thawalib Jakarta, 2026)
Low community participation, limited infrastructure, restricted access to education and healthcare, and insufficient routine services hinder the development of agricultural and MSME potentials, as well as the sustainable and inclusive growth of village communities. This community service aims to boost community capacity through a Participatory Action Research (PAR) approach by strengthening collaborative participation, independence, and the sustainable use of local resources. The methodology used was Participatory Action Research, which involved problem identification, joint planning, implementation of educational, religious, and health programs, and participatory evaluation, engaging the community as active partners throughout the entire process in a sustainable way. The program's outcomes show improved student understanding through tutoring, increased social awareness via anti-bullying seminars, and better Quran reading skills among children through religious activities. Community participation in joint activities has begun to grow, and planting medicinal and nutritional plants (TOGA) has promoted health awareness and the use of local resources. The program also enhanced social bonds within the community and expanded understanding of the village’s economic potential, although participation from some residents remains limited and needs further improvement. PAR-based community service effectively strengthens community capacity, participation, and the use of local resources, but it requires ongoing support and broader involvement. This program is important for fostering sustainable village development through community empowerment, local capacity building, and stronger collaboration among stakeholders.